The Effects of Some Anthropometric Features on Dynamic Balance - Suleyman Patlar; Oktay Cakmakcı; Ali Tatlıcı; Sercan Yılmaz (Selcuk University, 2020)
Purpose: Various neurophysiological and mechanical factors (such as height, weight, body composition, the base of support, the length and weight of each limb) can affect the balance. This study aims to examine the effect of some anthropometric features on balance. Material: Totally 22 healthy male athletes joined the study. Body weight and height were measured before the balance measurements of the athletes, and body mass indexes were calculated accordingly. Circumferential measurements and skinfold thickness were measured using a caliper. Balance measurements of the athletes were calculated with the Biodex Balance System with dominant legs. Results: In the study, while a significant positive correlation was found between body mass index body weight, knee joint diameters, thigh and calf circumference, and balance scores, no significant relationship was found between age, height, foot length, and foot width and all three balance scores Conclusions: It could be said that body weight, knee joint diameter, body mass index, thigh and circumference characteristics of the study were significantly related to the balance scores in the positive direction but not regarding age, height, foot length and width characteristics.